Interfacial intermetallic compound modification to extend the electromigration lifetime of copper pillar joints - Yang, Dongsheng; Huang, Yilong (Frontiers in Materials, 2023)
Electromigration (EM) is the massive metal atom transport due to electron flow, which could induce a disconnect in electronics. Due to the size of copper pillar bump reduction, the portion of interfacial intermetallic compound (IMC) in solder joints is increasing obviously. However, there is lack of systematical research on the effects of IMC on the EM lifetime of solder joints. In this paper, the interfacial IMC of copper pillar joints is modified to extend the electromigration lifetime. The growth rate of IMC in solder joints sample is calculated firstly. From 230 °C to 250 °C, the growth rate of IMC increases from 0.09 μm/min to 0.19 μm/min. With a longer reaction time, the IMC layers continuously grow. Then electromigration tests were conducted under thermo-electric coupling loading of 100 °C and 1.0×104 A/cm2. Compared with lifetime of thin and thick IMC samples, the lifetime of all IMC sample improved significantly. The lifetime of thin, thick, and all IMC samples is 400 min, 300 min, and 1200 min, respectively. The failure mechanism for the thin IMC sample is massive voids generation and aggregation at the interface between solder joints and pads. For the thick IMC sample, the IMC distance is short between cathode and anode in solder joints, leading to lots of crack create in the middle of solder joints. As the all IMC sample can greatly reduce the number of voids generated by crystal structure transforming, the lifetime extend obviously.